Optimisation of the crystallisation process through staggered cooling in a nonvibrating granular system - A. Escobar; R. E. Moctezuma; F. Donado (Scientific Reports)
Abstract We study experimentally the optimisation of the crystallisation process through a 2D-dimensional system of magnetic particles under an oscillating magnetic field. The time-dependent magnetic field fluidises the system, and by varying its magnitude, the effective temperature of the system is controlled. The system exhibits fluid-like behaviour when the effective temperature is high and evolves to a crystalline arrangement when the temperature is slowly lowered in linear cooling. We found that replacing the linear cooling path with a staggered one let us find the conditions to crystallise the system quicker than using linear cooling. We determine the minimum time required for the particles to find their minimum energy configuration at each temperature step. We found that the crystallisation time was considerably reduced using this method, which allowed us to optimise the crystallisation time.